FRAME REPRESENTATION OF LINGUOCULTURAL UNITS (Scientific journal of the Fergana State University, 2025)
This article is of interest because today, as never before, researchers pay attention to the problem of the relationship between language and culture, their interdependence and mutual influence. The paper considers frames, linguocultural units, the relationship between language and culture from the point of view of philological comparativism. Particular attention is paid to the structural frame-analysis of linguocultures, which allows us to identify seven types of frame, which is expressed in the ability of language to reflect the cultural and national mentality of its speakers.